Carbide slag fly ash concrete aerated block and preparation method thereof
By employing a preparation process involving nano-core-shell structured calcium aluminum silicon polymers and zwitterionic foam-stabilizing polymers, the problems of insufficient solid waste activity and poor foaming stability in carbide slag and fly ash concrete aerated blocks have been solved. This has enabled efficient utilization and performance improvement, optimized the production process, and enhanced the product's freeze-thaw cycle resistance and compressive strength.
Patent Information
- Application Number
- CN202511298772.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-11
- Publication Date
- 2025-12-12
- Estimated Expiration
- 2045-09-11
AI Technical Summary
In existing technologies, aerated concrete blocks made from carbide slag and fly ash suffer from insufficient solid waste cementitious activity, poor foaming stability, uneven product structure, and low production efficiency, making it difficult to achieve efficient utilization and performance improvement.
The preparation process employs a nano-core-shell structured calcium aluminum silicon polymer and a zwitterionic foam stabilizer polymer. Through interface engineering and biomimetic mineralization, a highly reactive nano-core-shell structure is formed. Combined with the zwitterionic foam stabilizer polymer, a stable bubble structure is formed at the gas-liquid interface. The raw material ratio and molding and curing process are optimized.
It significantly improves the coagulation activity of solid waste, the uniformity of bubble distribution and product performance, reduces production energy consumption, and improves production efficiency and overall product performance.
Smart Images

Figure BDA0005592310110000111 
Figure BDA0005592310110000121
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of building materials and solid waste resource utilization, and particularly relates to a calcium carbide slag and fly ash aerated concrete block and a preparation method thereof. BACKGROUND
[0002] With the rapid development of the construction industry and the acceleration of urbanization, aerated concrete blocks, as a new type of lightweight, thermal insulation and anti-seismic wall material, are widely used in residential, public buildings and other fields due to their excellent performance, and the market demand continues to grow. However, the production of traditional aerated concrete blocks mainly relies on natural resources such as natural sandstone and cement, and large-scale mining not only leads to the depletion of mineral resources, but also causes serious ecological damage and environmental pollution. At the same time, the industrial production of calcium carbide slag and fly ash and other solid wastes is increasing year by year, and the storage occupies a large amount of land resources, and the leakage of some harmful ingredients also pollutes the soil and water, which poses a serious threat to the ecological environment. Under this background, how to efficiently use industrial solid waste to replace part of the traditional raw materials to prepare high-performance building materials has become an important research direction to promote the development of circular economy and achieve the "double carbon" goal, and the research and development of calcium carbide slag and fly ash aerated concrete blocks has therefore attracted widespread attention.
[0003] At present, there are some attempts in the market to use calcium carbide slag and fly ash to prepare aerated concrete blocks. Calcium carbide slag is an industrial waste residue after the hydrolysis of calcium carbide to produce acetylene, and its main component is calcium hydroxide. Although its high alkalinity and low activity can replace part of the cement to some extent, the direct use of calcium carbide slag will lead to slow development of early strength and unstable setting time of aerated concrete blocks due to insufficient cementing activity. Fly ash is a discharge from coal-fired power plants, which contains a large amount of silicon and aluminum components, but its pozzolanic activity needs to be activated by activators to effectively play a role. In traditional processes, alkali activators or sulfate activators are often used alone, which has the problems of low activation efficiency and weak synergistic effect, resulting in limited fly ash content and difficulty in further improving the utilization rate of solid waste. In addition, the foaming process of aerated concrete blocks has very high requirements for bubble stability, and traditional processes often use aluminum powder as a foaming agent, which has a significant impact on foaming rate due to temperature and pH value. The uneven distribution of bubbles, string holes or collapsed mold phenomenon often occurs, resulting in loose internal structure and large bulk density fluctuations of the product, which is difficult to meet the technical requirements of high-strength aerated concrete blocks. The existing process also has optimization space in the curing process, such as unreasonable autoclave curing system that may lead to imperfect internal structure of the product, and long natural curing cycle that affects production efficiency. These factors jointly restrict the large-scale application and performance improvement of calcium carbide slag and fly ash aerated concrete blocks.
[0004] In view of the above technical bottleneck, in recent years, relevant researches have carried out exploration around raw material modification and process optimization. Some studies attempt to improve the activity of carbide slag and fly ash through mechanical grinding, chemical activation and other means, but mechanical grinding has high energy consumption and low efficiency, and the selection and ratio of chemical activator still need to be optimized; Some studies propose to add polymer additives to improve the fluidity of the slurry or the stability of the bubbles, but the existing additives are mostly single-function, which is difficult to meet the multiple requirements of enhancing cementation, controlling foaming and optimizing pore structure, and the preparation process of some polymers is complex and the cost is high, which limits its engineering application. Under this background, it is of great significance to develop a preparation technology of carbide slag and fly ash aerated concrete block which takes into account efficient utilization of solid waste, stable and controllable performance and simple process, for promoting the resource utilization of industrial solid waste, reducing the production cost of building materials and improving the comprehensive performance of products. Based on this demand, by designing the preparation process of nano core-shell structure calcium-aluminum-silicon polymer and zwitterionic stable bubble polymer, and optimizing the raw material ratio and forming and curing process, the problems of insufficient activity of solid waste, poor foaming stability and large fluctuation of product performance in traditional technology can be solved, and a new technical path is provided for the high-value application of carbide slag and fly ash aerated concrete block. SUMMARY
[0005] The purpose of the present application is to provide a carbide slag and fly ash aerated concrete block and a preparation method thereof, which solves the technical problems of insufficient cementing activity of solid waste, poor foaming stability, uneven product structure and low production process efficiency of existing carbide slag and fly ash aerated concrete block.
[0006] The present application realizes the above-mentioned purpose by the following technical solutions:
[0007] A carbide slag and fly ash aerated concrete block, comprising the following raw materials by weight:
[0008] Carbide slag: 150-300 parts by weight;
[0009] Fly ash: 600-750 parts by weight;
[0010] Gypsum: 20-50 parts by weight;
[0011] Silicate cement: 30-80 parts by weight;
[0012] Aluminum paste: 0.5-1.5 parts by weight;
[0013] Nano core-shell structure calcium-aluminum-silicon polymer: 5-25 parts by weight;
[0014] Zwitterionic stable bubble polymer: 1-5 parts by weight;
[0015] The preparation method of the nano core-shell structure calcium-aluminum-silicon polymer comprises: A1, dispersing fly ash in deionized water to form a uniform slurry, adding sodium silicate solution and sodium aluminate solution under high-speed shearing, adjusting pH to 11-12, and reacting at 70-72 DEG C; A2, subsequently, calcium nitrate solution and zinc sulfate are added to the slurry, the reaction temperature is maintained at 80-84 DEG C, and the reaction is continued; after the reaction is completed, centrifugal separation, ethanol washing are carried out to terminate the reaction, and finally vacuum drying is carried out at 60-64 DEG C, and grinding is carried out to pass through a sieve.
[0016] In the application, the preparation process of the nano core-shell structure calcium-aluminum-silicon polymer is a delicate interface engineering and biomimetic mineralization process. The reaction starts from the surface activation stage of fly ash particles. In an alkaline environment, the silicon and aluminate ions provided by sodium silicate and sodium aluminate will dissociate and recombine with the silicon-oxygen bonds and aluminum-oxygen bonds on the surface of fly ash, forming silicon and aluminum hydroxyl sites with higher reactivity. These newly generated active sites act as anchors, laying the molecular foundation for subsequent mineralization and deposition. The subsequently introduced calcium nitrate solution provides sufficient calcium ions, which, under the crystal form guiding effect of zinc sulfate, do not precipitate randomly but are directionally adsorbed and orderly arranged on the surface of fly ash particles. The zinc ions in zinc sulfate have a unique amphoteric characteristic, being able to coordinate with both silicate ions and calcium ions, like a molecular template guiding the epitaxial growth of hydrated calcium silicate in the form of a nano-thin layer on the surface of fly ash. This process simulates the controllable crystallization mechanism in biological mineralization, ultimately forming a composite structure with fly ash as the core and nano-hydrated calcium silicate as the shell. This core-shell design greatly increases the specific surface area and reactivity of the material. When added to the aerated block system, these nano core-shell particles become nucleation centers for the hydration reaction, accelerating the formation of hydrated calcium silicate gel and effectively improving the early strength development of the slurry.
[0017] According to the preferred embodiment of the application, in step A1, the reaction time at 70-72 DEG C is 2-4 h.
[0018] According to the preferred embodiment of the application, in step A2, the continuous reaction time is 4-6 h; the vacuum drying time at 60-64 DEG C is 24-30 h; and the grinding is carried out to pass through a 400-500 mesh sieve.
[0019] According to the preferred embodiment of the present application, the preparation method of the zwitterionic foam stabilizing polymer comprises: B1, under nitrogen protection, 2-(dimethylamino)ethyl methacrylate and 2-acrylamide-2-methylpropanesulfonic acid monomers are added in dimethyl sulfoxide as a solvent; after stirring and dissolving, azobisisobutyronitrile is added, and the reaction is carried out in an oil bath at 74-76℃ to obtain a crude product; B2, the crude product is added dropwise into ice ether for precipitation and separation, and the white flocculent precipitate is collected after filtration; the precipitate is redissolved in deionized water, and iodomethane is added, and the reaction is carried out at 40-42℃; after the reaction is completed, the dialysis bag is dialyzed to obtain a quaternary ammonium linear copolymer solution; 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide are added to the quaternary ammonium linear copolymer solution, and then ethylenediamine is added, and the reaction is carried out at room temperature; after the reaction is completed, the purification is carried out again by dialysis, and finally freeze-drying is carried out.
[0020] In the present application, the synthesis of the zwitterionic foam stabilizing polymer is a multi-step molecular design and assembly process. Firstly, a linear polymer skeleton containing tertiary amine groups and sulfonic acid groups is synthesized by free radical copolymerization, and this skeleton itself has the rudiment of zwitterion. Then in the quaternization reaction, iodomethane undergoes nucleophilic substitution reaction with the tertiary amine group to convert the tertiary amine into a quaternary ammonium salt cation, at this time the polymer chain permanently carries positive and negative charges, forming a true zwitterionic structure. This special molecular structure makes it exhibit strong hydrophilicity and unique antipolyelectrolyte effect in aqueous solution. The most critical step is the crosslinking reaction, ethylenediamine acts as a bifunctional crosslinking agent, and the two ends of the amino group react with the activated carboxyl group on the polymer chain to form an amide, thereby building a stable three-dimensional network structure between different polymer chains. This crosslinked network not only improves the mechanical strength of the polymer, but more importantly enables it to form a molecular film with high surface elasticity and viscosity at the gas-liquid interface. When the gas is generated in the aerated block, this zwitterionic polymer can quickly adsorb to the interface of the hydrogen gas bubble, and its three-dimensional network structure can effectively resist liquid film drainage and gas diffusion, while its zwitterionic property can resist the destruction of high calcium ion concentration in the system, thereby stabilizing the bubble structure and forming uniform and fine closed pores.
[0021] According to the preferred embodiment of the present application, in step B1, the reaction time in the oil bath at 74-76℃ is 8-10h.
[0022] According to the preferred embodiment of the present application, in step B2, the reaction time at 40-42℃ is 12-14h.
[0023] The present application also provides a preparation method of the calcium carbide slag and fly ash aerated block, and the steps comprise:
[0024] S1, the carbide slag, fly ash, gypsum and Portland cement are put into a forced stirrer to dry mix to be uniform, to obtain dry materials; then, the nano core-shell structure calcium-aluminum-silicon polymer and the amphoteric ion type foam stabilizing polymer are dissolved in water, and are fully stirred to form a modified aqueous solution;
[0025] S2, the modified aqueous solution is poured into the forced stirrer to mix with the dry materials, and is stirred to form a uniform slurry; then, the aluminum paste is added into the slurry, is uniformly dispersed by high-speed stirring, and then the slurry is poured into a mold which is pre-coated with a release agent, and is cured at 60-64 DEG C under static air curing; after the green body is hardened, the mold is demolded, and is cut to obtain a green body;
[0026] S3, the cut green body is put into a steam autoclave, and is autoclaved under the condition that the saturated steam pressure is 1.0-1.2 MPa and the temperature is 180-190 DEG C; after being taken out of the autoclave, the green body is cured naturally.
[0027] In the present application, the preparation of the carbide slag-fly ash aerated block is a complex process of multiple components and multiple stages. In the initial mixing stage, the calcium hydroxide provided by the carbide slag and the active silicon-aluminum components in the fly ash begin to have a pozzolanic reaction under an alkaline environment, and the addition of gypsum adjusts the setting time and promotes the generation of ettringite. The addition of the nano core-shell structure calcium-aluminum-silicon polymer is like the input of numerous micro-reactors, and the nano calcium silicate shell layer on the surface of the nano core-shell structure provides abundant nucleation sites for the system, greatly accelerates the progress of the hydration reaction, and makes the slurry quickly obtain early strength. At the same time, the amphoteric ion type foam stabilizing polymer is fully dissolved and dispersed in the slurry, and its unique amphoteric ion structure and three-dimensional network characteristics enable it to form a strong adsorption film at the gas-liquid interface. When the aluminum paste reacts with the alkaline environment to produce hydrogen, these bubbles are firmly stabilized by the elastic film formed by the amphoteric ion polymer to form uniformly distributed micro-bubbles. In the static curing stage, the nano core-shell particles continue to promote the development of the hydration reaction, so that the strength of the green body is sufficient for cutting; and in the autoclave curing stage, the high temperature and high pressure conditions greatly promote the depth of the pozzolanic reaction, and a large amount of well-crystallized tobermorite and other hydration products are generated, which together with the stable pore structure constitute the final strength skeleton of the aerated block. The three main components: carbide slag-fly ash matrix, nano core-shell reinforcing agent and amphoteric ion stabilizing agent, through cooperation, finally form an aerated block product with excellent mechanical properties, uniform pore structure and good durability.
[0028] According to the preferred embodiment of the present application, in step S1, the dry mixing time is 3-5 min.
[0029] According to the preferred embodiment of the present application, in step S2, the high-speed stirring time is 30-45 s; and the static air curing time at 60-64 DEG C is 2-3 h.
[0030] According to a preferred embodiment of the present application, the autoclaved curing time in step S3 is 8-10 hours.
[0031] The present application has the following advantages:
[0032] The present application has the following advantages:
[0033] In terms of product performance, the zwitterionic foam stabilizing polymer stabilizes the bubble surface through positive and negative charge groups, inhibits coalescence and rupture, and combines with the bidirectional regulation of nano polymer on the viscosity of the slurry (reducing the stirring viscosity and improving the static setting thixotropy), making the bubble distribution more uniform and the internal structure regular polyhedron. Compared with traditional processes, the freeze-thaw cycle resistance, compressive strength of aerated block is improved, the drying shrinkage is reduced, and the overall performance is significantly improved.
[0034] In terms of process optimization, the initial stability of the slurry is improved by adjusting the dry mixing time, modifying the water solution ratio and stirring speed; the precise temperature control in the static setting and gas evolution stage shortens the curing time and avoids cracking; the steam parameters in the autoclaved curing optimize the strength development, and the natural curing reduces the water evaporation stress. The overall process improves the daily production capacity of the production line, reduces the unit energy consumption, and synchronously improves the production efficiency and economic benefits. DETAILED DESCRIPTION
[0035] The following detailed description is only used to further illustrate the present application and cannot be understood as limiting the scope of protection of the present application. Those skilled in the art can make some non-essential improvements and adjustments to the present application based on the above application content.
[0036] The main related equipment and material suppliers in China are as follows:
[0037] The calcium carbide slag is purchased from Xinjiang Zhongtai Mining and Metallurgy Co., Ltd.
[0038] The fly ash is purchased from Datang International Power Generation Co., Ltd. Douhe Power Plant.
[0039] The gypsum is purchased from Shandong Taishan Gypsum Co., Ltd.
[0040] The portland cement is purchased from Anhui Hailuo Cement Co., Ltd.
[0041] The aluminum powder paste is purchased from Henan Branch of China Aluminum Corporation.
[0042] The sodium silicate solution is purchased from Guizhou Hongxing Development Co., Ltd.
[0043] The sodium metaaluminate solution is purchased from Shandong Haihua Co., Ltd.
[0044] The calcium nitrate solution is purchased from Hubei Xingfa Chemical Industry Group Co., Ltd.
[0045] The zinc sulfate is purchased from Gudao Zinc Industry Co., Ltd.
[0046] The nitrogen is purchased from Hangzhou Hangyang Co., Ltd.
[0047] The dimethyl sulfoxide is purchased from Hubei Guangji Pharmaceutical Co., Ltd.
[0048] The 2-(dimethylamino)ethyl methacrylate is purchased from Sinopharm Chemical Reagent Co., Ltd.
[0049] The 2-acrylamide-2-methylpropanesulfonic acid monomer is purchased from Shengli Oilfield Zhongsheng Environmental Protection Co., Ltd.
[0050] The azobisisobutyronitrile is purchased from Tianjin Lianlong New Material Co., Ltd.
[0051] The diethyl ether is purchased from Jiangsu Qiangsheng Functional Chemical Co., Ltd.
[0052] The iodomethane is purchased from Zhejiang Xinhengcheng Co., Ltd.
[0053] The 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride is purchased from Shanghai Yuanye Biotechnology Co., Ltd.
[0054] The N-hydroxysuccinimide is purchased from Shanghai Yuanye Biotechnology Co., Ltd.
[0055] The ethylenediamine is purchased from Jiangsu Feixing Chemical Co., Ltd.
[0056] The forced stirrer is purchased from Sinoma Intelligent Equipment Co., Ltd.
[0057] The mold is purchased from Foshan Keda Manufacturing Co., Ltd.
[0058] The release agent is purchased from Jiangsu Risonic Chemical Co., Ltd.
[0059] The steam autoclave is purchased from Dalian Jinzhou Heavy Machine Group Co., Ltd.
[0060] Example 1
[0061] The raw material composition of the calcium carbide slag fly ash aerated concrete block is as follows: 225g of calcium carbide slag, 675g of fly ash, 35g of gypsum, 55g of Portland cement, 1.0g of aluminum paste, 15g of nano core-shell structure calcium aluminum silicon polymer, and 3g of amphoteric ion type foam stabilizing polymer. The preparation method of the nano core-shell structure calcium aluminum silicon polymer is as follows: first, prepare the reaction raw materials, take 50g of fly ash, 500ml of deionized water, 100ml of 1mol / L sodium silicate solution, 50ml of 0.5mol / L sodium metaaluminate solution, 200ml of 0.2mol / L calcium nitrate solution, and 5g of zinc sulfate; disperse 50g of fly ash in 500ml of deionized water, use a high-speed dispersing machine to stir at a speed of 2000rpm for 10 minutes to form a uniform slurry; slowly add 100ml of sodium silicate solution and 50ml of sodium metaaluminate solution under continuous high-speed shearing, and the feeding time is 15 minutes; adjust the pH of the slurry to 11.5 with 10% sodium hydroxide solution, transfer the reaction container to a constant temperature water bath, and react at 71℃ for 3 hours while maintaining the stirring speed at 300rpm; after the reaction is completed, the temperature of the system is raised to 82℃, and 200ml of calcium nitrate solution and 5g of zinc sulfate are slowly added under stirring, and the feeding time is 20 minutes; after the feeding is completed, continue to react at 82℃ for 5 hours, and maintain the stirring speed at 300rpm during the reaction; after the reaction is completed, the slurry is transferred to a centrifuge and centrifuged at a speed of 8000rpm for 10 minutes, and the supernatant is discarded; the precipitate is washed with 200ml of ethanol three times, and centrifuged after each washing to terminate the reaction and remove impurities; the washed precipitate is transferred to a vacuum drying oven and dried at 62℃ for 28 hours; the dried block-shaped product is placed in a planetary ball mill and ground at a speed of 350rpm for 2 hours, and then sieved through a 450 mesh sieve to obtain a white powder of nano core-shell structure calcium aluminum silicon polymer, which is sealed and stored for use.
[0062] The preparation method of the zwitterionic foam stabilizing polymer is as follows: first, prepare the reaction raw materials, weigh 25 g of 2-dimethylaminoethyl methacrylate, 25 g of 2-acrylamide-2-methylpropanesulfonic acid monomer, 0.5 g of azobisisobutyronitrile, 15 g of iodomethane, 2 g of 1-3-dimethylaminopropyl-3-ethyl carbodiimide hydrochloride, 1.2 g of N-hydroxysuccinimide, 3 g of ethylenediamine, 200 ml of dimethyl sulfoxide, and 500 ml of deionized water; add 200 ml of dimethyl sulfoxide into a 250 ml three-necked flask, and protect by passing nitrogen for 15 minutes to remove oxygen; add 25 g of 2-dimethylaminoethyl methacrylate and 25 g of 2-acrylamide-2-methylpropanesulfonic acid monomer, and stir at a speed of 500 rpm until completely dissolved; add 0.5 g of azobisisobutyronitrile, continue to protect by passing nitrogen, and transfer the reaction flask to a 75°C oil bath, and react at a speed of 300 rpm for 9 hours; after the reaction is completed, cool the reaction liquid to room temperature, and add dropwise into 2000 ml of ice ether under stirring, and white flocculent precipitate is precipitated; after standing for 30 minutes, filter and collect the white flocculent precipitate, and wash with 100 ml of cold ether for three times; dissolve the precipitate in 500 ml of deionized water, add 15 g of iodomethane, transfer the reaction flask to a 41°C water bath, and react at a speed of 300 rpm for 13 hours; after the reaction is completed, transfer the reaction liquid to a dialysis bag with a molecular weight cut-off of 3500, and dialyze in deionized water for 48 hours, and change the water every 6 hours; after obtaining the quaternary ammonium linear copolymer solution, add 2 g of 1-3-dimethylaminopropyl-3-ethyl carbodiimide hydrochloride and 1.2 g of N-hydroxysuccinimide, and stir at a speed of 500 rpm for 30 minutes to activate the carboxyl group; add 3 g of ethylenediamine, and react at a speed of 300 rpm at room temperature for 12 hours; after the reaction is completed, transfer the reaction liquid into a dialysis bag again, dialyze in deionized water for 72 hours, and change the water every 8 hours; finally, freeze-dry the dialyzed solution for 48 hours to obtain the zwitterionic foam stabilizing polymer product in the form of white solid, and seal and store for use.
[0063] The preparation method of the aerated block comprises the following steps: firstly, preparing raw materials, taking 225 g of carbide slag, 675 g of fly ash, 35 g of gypsum, 55 g of portland cement, 1.0 g of aluminum paste, 15 g of prepared nano core-shell structure calcium aluminum silicon polymer, and 3 g of prepared amphoteric ion type foam stabilizing polymer; the carbide slag, fly ash, gypsum and portland cement are put into a forced stirrer, and dry mixing is performed at a speed of 400 rpm for 4 minutes until uniform, to obtain dry materials; 15 g of nano core-shell structure calcium aluminum silicon polymer and 3 g of amphoteric ion type foam stabilizing polymer are dissolved in 200 ml of deionized water at room temperature, and a magnetic stirrer is used to stir at a speed of 800 rpm for 5 minutes to form a uniform modified aqueous solution; the modified aqueous solution is poured into the forced stirrer to mix with the dry materials, and stirring is performed at a speed of 600 rpm for 3 minutes to form a uniform slurry; 1.0 g of aluminum paste is added to the slurry, and high-speed stirring is performed at a speed of 1200 rpm for 38 seconds to uniformly disperse the aluminum paste; the slurry is immediately poured into a 100 mm*100 mm*100 mm steel mold coated with a release agent in advance, and the mold is gently vibrated after pouring to remove air bubbles; the mold is transferred to a 62℃ curing room for static standing and gas evolution curing for 2.5 hours; after the green body is hardened, the mold is demolded, a steel wire cutting machine is used for cutting to obtain a green body with a standard size; the cut green body is sent into an autoclave, the temperature is raised to 185℃ at a rate of 1.5℃ / min, and the pressure is kept at 1.1 MPa saturated steam pressure for 9 hours; after the curing is completed, the pressure and temperature are reduced at a rate of 0.7℃ / min, and after the autoclave is taken out, the product aerated block is obtained after natural curing at room temperature for 28 days.
[0064] Example 2
[0065] The specific implementation is the same as that in Example 1, except that one kind of carbide slag-fly ash aerated concrete block, the raw material composition is as follows: carbide slag 150 g, fly ash 600 g, gypsum 20 g, portland cement 80 g, aluminum paste 1.5 g, nano core-shell structure calcium aluminum silicon polymer 25 g, and amphoteric ion type foam stabilizing polymer 5 g. The preparation method of the nano core-shell structure calcium aluminum silicon polymer is as follows: 60 g of fly ash is first dispersed in 500 ml of deionized water to form a uniform slurry, 120 ml of 1 mol / L sodium silicate solution and 60 ml of 0.5 mol / L sodium metaaluminate solution are added under high-speed shearing, the pH is adjusted to 12 with sodium hydroxide solution, and the reaction is carried out at 72℃ for 2 hours; then, 0.2 mol / L calcium nitrate solution 250 ml is added to the slurry under stirring, together with 6 g of zinc sulfate, the reaction temperature is maintained at 84℃, and the reaction is continued for 4 hours; after the reaction is completed, centrifugal separation is performed, and the product is washed with ethanol three times to terminate the reaction, and finally vacuum drying is performed at 64℃ for 24 hours, the product is ground through a 500 mesh sieve, and a white powder is obtained.
[0066] The preparation method of the zwitterionic stabilizing polymer is as follows: under nitrogen protection, 200 ml dimethyl sulfoxide is used as a solvent, 30 g 2-dimethylaminoethyl methacrylate and 20 g 2-acrylamide-2-methylpropanesulfonic acid monomer are added; after stirring and dissolving, 0.6 g azobisdimethyl isobutyronitrile is added, and the reaction is carried out at 76 °C in an oil bath for 8 hours to obtain a crude product; the crude product is added dropwise into 2000 ml ice ether for precipitation and separation, and the white flocculent precipitate is collected after filtration; the precipitate is redissolved in 500 ml deionized water, and 18 g iodomethane is added, and the reaction is carried out at 42 °C for 12 hours; after the reaction is completed, the solution is dialyzed through a dialysis bag with a molecular weight cut-off of 3500 for 48 hours to obtain a quaternary ammonium linear copolymer solution; 2.5 g 1-3-dimethylaminopropyl-3-ethyl carbodiimide hydrochloride and 1.5 g N-hydroxysuccinimide are added to the solution, stirred and activated for 30 minutes, and then 4 g ethylenediamine is added, and the reaction is carried out at room temperature for 12 hours; after the reaction is completed, the solution is dialyzed again for 72 hours, and finally the white solid product is obtained by freeze-drying. The preparation method of the aerated block comprises: the carbide slag, fly ash, gypsum and Portland cement are put into a forced stirrer to dry mix for 3 minutes at a speed of 400 rpm to obtain dry materials; then, the nano core-shell structure calcium-aluminum-silicon polymer and the zwitterionic stabilizing polymer are dissolved in 200 ml water to form a modified aqueous solution after being stirred for 5 minutes; the modified aqueous solution is poured into the forced stirrer to mix with the dry materials, and the mixture is stirred at a speed of 600 rpm for 3 minutes to form a uniform slurry; then, the aluminum paste is added to the slurry, and the slurry is stirred at a high speed of 1200 rpm for 30 seconds to uniformly disperse the aluminum paste, and then the slurry is poured into a mold coated with a release agent in advance, and the slurry is cured at 64 °C for 2 hours; after the green body is hardened, it is demolded, cut to obtain a green body; the cut green body is put into a steam autoclave, and the steam autoclave is cured at a saturated steam pressure of 1.2 MPa and a temperature of 190 °C for 8 hours; after the autoclave is taken out, the product is obtained after natural curing for 28 days.
[0067] Example 3
[0068] The specific implementation is the same as example 1, except that a carbide slag fly ash aerated concrete block is prepared from the following raw materials: 300 g of carbide slag, 750 g of fly ash, 50 g of gypsum, 30 g of Portland cement, 0.5 g of aluminum paste, 5 g of nano core-shell calcium-aluminum-silicon polymer, and 1 g of amphoteric ion type foam stabilizing polymer. The nano core-shell calcium-aluminum-silicon polymer is prepared by first dispersing 40 g of fly ash in 500 ml of deionized water to form a uniform slurry, and then adding 80 ml of a 1 mol / L sodium silicate solution and 40 ml of a 0.5 mol / L sodium meta-aluminate solution under high shear, adjusting the pH to 11 with a sodium hydroxide solution, and reacting at 70°C for 4 hours. Subsequently, 150 ml of a 0.2 mol / L calcium nitrate solution is added to the slurry along with 4 g of zinc sulfate under stirring, and the reaction temperature is maintained at 80°C for 6 hours. After the reaction is completed, the product is separated by centrifugation, washed with ethanol three times to terminate the reaction, and finally dried under vacuum at 60°C for 30 hours, ground through a 400 mesh sieve, and obtained as a white powder. The amphoteric ion type foam stabilizing polymer is prepared by adding 20 g of 2-dimethylaminoethyl methacrylate and 30 g of 2-acrylamido-2-methylpropanesulfonic acid monomer to 200 ml of dimethyl sulfoxide as a solvent under nitrogen protection. After stirring and dissolving, 0.4 g of azobisisobutyronitrile is added, and the reaction is carried out at 74°C for 10 hours to obtain a crude product. The crude product is added dropwise to 2000 ml of ice ether for precipitation, and the white flocculent precipitate is collected after filtration. The precipitate is redissolved in 500 ml of deionized water, and 12 g of iodomethane is added, and the reaction is carried out at 40°C for 14 hours. After the reaction is completed, the product is purified by dialysis for 48 hours using a dialysis bag with a molecular weight cutoff of 3500, and a quaternary ammonium linear copolymer solution is obtained. 1.5 g of 1-3-dimethylaminopropyl-3-ethylcarbodiimide hydrochloride and 1.0 g of N-hydroxysuccinimide are added to the solution, and after stirring and activating for 30 minutes, 2 g of ethylenediamine is added, and the reaction is carried out at room temperature for 12 hours. After the reaction is completed, the product is purified again by dialysis for 72 hours, and finally obtained as a white solid after freeze-drying.The preparation method of the aerated block comprises: putting carbide slag, fly ash, gypsum and Portland cement into a forced stirrer to dry mix for 5 minutes at a speed of 400 rpm until uniform to obtain dry materials; then, dissolving nano core-shell structure calcium aluminum silicon polymer and amphoteric ion type foam stabilizing polymer in 200 ml of water, stirring for 5 minutes to form a modified aqueous solution; pouring the modified aqueous solution into the forced stirrer to mix with the dry materials, stirring at a speed of 600 rpm for 3 minutes to form a uniform slurry; then, adding aluminum powder paste into the slurry, uniformly dispersing at a high speed of 1200 rpm for 45 seconds, pouring the slurry into a mold coated with a release agent in advance, and curing at 60°C for 3 hours; after the green body hardens, it is demolded, cut to obtain a green body; the cut green body is sent into an autoclave, and autoclave curing is performed at a saturated steam pressure of 1.0 MPa and a temperature of 180°C for 10 hours; after taking out of the autoclave, the finished product is obtained after natural curing for 28 days.
[0069] Comparative Example 1
[0070] The specific implementation is the same as that of Example 1, except that one kind of carbide slag fly ash aerated concrete block, the raw material composition is as follows: carbide slag 225g, fly ash 675g, gypsum 35g, Portland cement 55g, aluminum powder paste 1.0g. No nano core-shell structure calcium aluminum silicon polymer and amphoteric ion type foam stabilizing polymer are added. The preparation method of the aerated block comprises: putting carbide slag, fly ash, gypsum and Portland cement into a forced stirrer to dry mix for 4 minutes at a speed of 400 rpm until uniform to obtain dry materials; then, adding 200 ml of water into the forced stirrer to mix with the dry materials, stirring at a speed of 600 rpm for 3 minutes to form a uniform slurry; then, adding aluminum powder paste into the slurry, uniformly dispersing at a high speed of 1200 rpm for 38 seconds, pouring the slurry into a mold coated with a release agent in advance, and curing at 62°C for 2.5 hours; after the green body hardens, it is demolded, cut to obtain a green body; the cut green body is sent into an autoclave, and autoclave curing is performed at a saturated steam pressure of 1.1 MPa and a temperature of 185°C for 9 hours; after taking out of the autoclave, the finished product is obtained after natural curing for 28 days.
[0071] Comparative Example 2
[0072] The specific implementation of Example 1 is different, that is, a calcium carbide slag fly ash concrete aerated block, the raw material composition is as follows: calcium carbide slag 225g, fly ash 675g, gypsum 35g, Portland cement 55g, aluminum paste 1.0g, nano core-shell structure calcium aluminum silicon polymer 15g. No zwitterionic foam stabilizing polymer is added. The preparation method of the nano core-shell structure calcium aluminum silicon polymer is the same as that of Example 1. The preparation method of the aerated block includes: the calcium carbide slag, fly ash, gypsum and Portland cement are put into a forced stirrer to dry mix for 4 minutes at a speed of 400 rpm until uniform, to obtain dry materials; then, the nano core-shell structure calcium aluminum silicon polymer is dissolved in 200ml water, and stirred for 5 minutes to form a modified aqueous solution; pour the modified aqueous solution into the forced stirrer and mix with the dry materials, stir at a speed of 600 rpm for 3 minutes to form a uniform slurry; then, the aluminum paste is added to the slurry, and high-speed stirring is carried out at a speed of 1200 rpm for 38 seconds to make it uniformly dispersed, then the slurry is poured into a mold coated with a release agent in advance, and cured at 62°C for 2.5 hours. After the body hardens, it is demolded, cut to obtain a blank; the cut blank is sent into a steam autoclave, and autoclaved at a saturated steam pressure of 1.1MPa and a temperature of 185°C for 9 hours; after taking out of the autoclave, it is naturally cured for 28 days to obtain the finished product.
[0073] Comparative Example 3
[0074] The specific implementation of Example 1 is different, that is, a calcium carbide slag fly ash concrete aerated block, the raw material composition is as follows: calcium carbide slag 225g, fly ash 675g, gypsum 35g, Portland cement 55g, aluminum paste 1.0g, nano core-shell structure calcium aluminum silicon polymer 15g. No zwitterionic foam stabilizing polymer is added. The preparation method of the nano core-shell structure calcium aluminum silicon polymer is the same as that of Example 1. The preparation method of the aerated block includes: the calcium carbide slag, fly ash, gypsum and Portland cement are put into a forced stirrer to dry mix for 4 minutes at a speed of 400 rpm until uniform, to obtain dry materials; then, the nano core-shell structure calcium aluminum silicon polymer is dissolved in 200ml water, and stirred for 5 minutes to form a modified aqueous solution; pour the modified aqueous solution into the forced stirrer and mix with the dry materials, stir at a speed of 600 rpm for 3 minutes to form a uniform slurry; then, the aluminum paste is added to the slurry, and high-speed stirring is carried out at a speed of 1200 rpm for 38 seconds to make it uniformly dispersed, then the slurry is poured into a mold coated with a release agent in advance, and cured at 62°C for 2.5 hours. After the body hardens, it is demolded, cut to obtain a blank; the cut blank is sent into a steam autoclave, and autoclaved at a saturated steam pressure of 1.1MPa and a temperature of 185°C for 9 hours; after taking out of the autoclave, it is naturally cured for 28 days to obtain the finished product.
[0075] Performance test
[0076] The aerated blocks prepared according to Examples 1-3 and Comparative Examples 1-3; the performance tests were carried out according to the following methods, and all the test pieces were conditioned to constant weight at a standard environment of temperature 20±2℃ and relative humidity 50%±5% before starting the tests. The dry density test was carried out according to GB / T 11969-2008 "Test Methods for Autoclaved Aerated Concrete", the test piece was placed in a forced air drying oven, and dried at a temperature of 105±5℃ until the mass difference was less than 0.2% for two consecutive times, which was the constant weight, then removed and cooled to room temperature in a desiccator, the mass was measured using an electronic balance with a precision of 0.1g, the size of the test piece was measured using a vernier caliper, and the volume was calculated, and finally the dry density value was obtained. The compressive strength test was carried out according to GB / T 11971-1997 "Test Methods for Mechanical Properties of Aerated Concrete", a WAW-1000 type microcomputer controlled electro-hydraulic servo universal testing machine was used, and the test piece was loaded at a rate of 2.0±0.5kN / s until it was destroyed, and the maximum load value was recorded, and the arithmetic average of six test pieces was taken as the compressive strength calculation result, and if the strength value of an individual test piece deviated from the average value by more than 20%, it was rejected. The drying shrinkage value test was carried out according to GB / T 11972-1997 "Test Methods for Drying Shrinkage of Aerated Concrete", the test piece was placed in a constant temperature and humidity box at a temperature of 20±2℃ and a relative humidity of 43%±2%, and the length change of the test piece was measured using an outside diameter micrometer and a length comparator at 1 day, 3 days, 7 days, 14 days, 21 days and 28 days, respectively, and before measurement, the test piece was taken out of the constant temperature and humidity box and the measurement was completed within 2 minutes, the drying shrinkage value was calculated according to the formula and the average value of three test pieces was taken. The thermal conductivity test was carried out according to GB / T 10294-2008 "Determination of Steady-State Thermal Resistance and Related Properties of Thermal Insulation - Guarded Hot Plate Method", using a DPI-03 type flat plate thermal conductivity tester, the test was carried out at an average temperature of 25℃, the surface of the test piece required to be smooth and flat, and to be in good contact with the hot plate, the hot plate temperature was 30℃ and the cold plate temperature was 20℃ during the test, and the data was recorded after the temperature was stable for 2 hours. The water absorption rate test was carried out according to GB / T 11973-1997 "Test Methods for Water Absorption of Aerated Concrete", the dry test piece was completely immersed in water at 20±5℃, the water surface was 30mm higher than the surface of the test piece, and after 24 hours of soaking, the surface water was wiped off with a wet towel and immediately weighed, and the water absorption rate was calculated. The pore size distribution analysis was carried out by mercury intrusion method, using an AutoPore Iv 9510 type automatic mercury intrusion tester, about 3g of sample was vacuum degassed at 100℃ for 4 hours, and then measured in the pressure range of 0.5-30000psi, the pore size distribution was calculated by Washburn equation, and the most probable pore size and average pore size were recorded. Each test item was strictly prepared according to the standard requirements and tested, and the average value of more than three effective test pieces was taken for all data to ensure the accuracy and reliability of the test results.
[0077] Performance test results:
[0078] Table 1: Performance test results of each example and comparative example
[0079]
[0080]
[0081] From Table 1, based on the comparison and analysis of the test data of the examples and the comparative examples, the four technical problems of the existing carbide slag and fly ash aerated concrete block are effectively solved by the synergistic use of the nano core-shell calcium aluminum silicon polymer and the zwitterionic foam stabilizing polymer in the examples 1-3. First, for the problem of insufficient solid waste cementitious activity, the nano core-shell calcium aluminum silicon polymer as a high-efficiency nucleating agent significantly promotes the pozzolanic reaction of calcium hydroxide in the carbide slag and the active components of fly ash, so that the compressive strength of the example group (5.25-5.82 MPa) is increased by more than 68% compared with that of the comparative example 1 (3.12 MPa) without adding any modifier, and even in the example 3 with the least amount of cement, it still maintains a high strength, which proves that the cementitious activity of the solid waste material is fully activated. Second, for the problem of poor foaming stability, the zwitterionic foam stabilizing polymer stabilizes the gas evolution process by forming a high-strength interfacial film, so that the example group obtains a uniform and fine pore structure (average pore size 0.32-0.38 μm), which is much better than that of the comparative example 1 (0.82 μm), and the water absorption is reduced by about 20%, and the bubble independent sealing property is significantly improved. Third, for the problem of uneven product structure, the synergistic effect of the two modifiers ensures the matching of the hydration reaction and the gas evolution process, so that the uniformity of the body structure is greatly improved, and the drying shrinkage value (0.43-0.51 mm / m) of the example group is reduced by about 40-50% compared with that of the comparative example 1 (0.86 mm / m), avoiding the cracking problem caused by uneven shrinkage. Finally, for the problem of low production process efficiency, the nano core-shell polymer accelerates the early hydration, so that the body can reach the cutting strength in a short time, shortening the static curing time, and the uniform structure reduces the waste rate after autoclave curing, improving the production efficiency. The performance of the comparative examples 2 and 3 with only a single modifier is better than that of the comparative example 1 but significantly lower than that of the example group, fully proving the indispensable synergistic effect of the two modifiers in optimizing the hydration process and stabilizing the bubble structure, thereby improving the mechanical properties, durability and production reliability of the aerated concrete block product as a whole.
[0082] The above examples only express several embodiments of the present application, and the description is more specific and detailed, but it should not be understood as limiting the scope of the present patent. It should be noted that for ordinary skilled persons in the art, without departing from the concept of the present application, a number of modifications and improvements can be made, which are within the scope of protection of the present application.
Claims
1. A calcium carbide slag fly ash aerated concrete block, characterized in that, The raw materials include the following weight parts: Carbide slag: 150-300 parts by weight; Fly ash: 600-750 parts by weight; Gypsum: 20-50 parts by weight; Silicate cement: 30-80 parts by weight; Aluminum paste: 0.5-1.5 parts by weight; Nano core-shell calcium-aluminum-silicon polymer: 5-25 parts by weight; Zwitterionic foam stabilizing polymer: 1-5 parts by weight; The preparation method of the nano core-shell calcium-aluminum-silicon polymer includes: A1, dispersing fly ash in deionized water to form a uniform slurry, adding sodium silicate solution and sodium metaaluminate solution under high-speed shearing, adjusting the pH to 11-12, and reacting at 70-72℃; A2, subsequently, adding calcium nitrate solution and zinc sulfate to the slurry, maintaining the reaction temperature at 80-84℃, and continuously reacting; after the reaction is completed, centrifugal separation, ethanol washing to terminate the reaction, and finally vacuum drying at 60-64℃, and grinding and sieving.
2. The calcium carbide slag fly ash aerated concrete block according to claim 1, characterized in that, In step A1, the reaction time at 70-72℃ is 2-4h.
3. The calcium carbide slag fly ash aerated concrete block according to claim 1, characterized in that, In step A2, the continuous reaction time is 4-6h; the vacuum drying time at 60-64℃ is 24-30h; and the grinding and sieving through a 400-500 mesh sieve.
4. The carbide slag fly ash aerated concrete block according to claim 1, characterized in that, The preparation method of the zwitterionic foam stabilizing polymer includes: B1, under nitrogen protection, using dimethyl sulfoxide as the solvent, adding 2-(dimethylamino) ethyl methacrylate and 2-acrylamido-2-methylpropanesulfonic acid monomers; after stirring and dissolving, adding azobisisobutyronitrile, and reacting in an oil bath at 74-76℃ to obtain a crude product; B2, adding the crude product dropwise into ice ether for precipitation and separation, collecting the white flocculent precipitate after filtration; redissolving the precipitate in deionized water, adding iodomethane, and reacting at 40-42℃; after the reaction is completed, dialysis is performed through a dialysis bag to obtain a quaternized linear copolymer solution; adding 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide to the quaternized linear copolymer solution, and then adding ethylenediamine, and stirring and reacting at room temperature; after the reaction is completed, dialysis purification is performed again, and finally freeze-drying is performed.
5. The carbide slag fly ash aerated concrete block according to claim 4, characterized in that, In step B1, the reaction time in the oil bath at 74-76℃ is 8-10h.
6. The carbide slag fly ash aerated concrete block according to claim 4, characterized in that, In step B2, the reaction time at 40-42℃ is 12-14h.
7. A method for producing the calcium carbide slag fly ash aerated concrete block according to any one of claims 1 to 6, characterized by the steps of It includes: S1, putting carbide slag, fly ash, gypsum, and silicate cement into a forced stirrer for dry mixing until uniform to obtain dry materials; Subsequently, dissolving the nano core-shell calcium-aluminum-silicon polymer and the zwitterionic foam stabilizing polymer in water, and fully stirring to form a modified aqueous solution; S2, pouring the modified aqueous solution into the forced stirrer to mix with the dry materials, and stirring to form a uniform slurry; then, adding aluminum paste to the slurry, stirring at high speed to uniformly disperse, pouring the slurry into a mold previously coated with a release agent, and standing for gas curing at 60-64℃; after the green body hardens, demolding, and cutting to obtain a green body; S3, putting the cut green body into a steam autoclave for autoclave curing under the conditions of a saturated steam pressure of 1.0-1.2MPa and a temperature of 180-190℃; after taking out, natural curing is performed.
8. The preparation method according to claim 7, characterized in that, In step S1, the dry mixing time is 3-5min.
9. The preparation method according to claim 7, characterized in that, In step S2, the high-speed stirring time is 30-45s; the static standing gasification curing time at 60-64℃ is 2-3h.
10. The method of claim 7, wherein, In step S3, the steam pressure curing time is 8-10h.
Citation Information
Patent Citations
Mixture containing quaternary ammonium compound and its use
CN101801888A
Carbide slag-based high-solid-carbon-content non-autoclaved aerated concrete and preparation method thereof
CN114988835A
Method for preparing lightweight high-strength aerated block by completely replacing quicklime with carbide slag
CN118324484A
Nano-external wall paint and its production method
CN1651529A
Static electricity removing steam curing device for aerated bricks
CN220593544U
Cited By
High-strength porous water storage type waste gas treatment base material and preparation method thereof
CN121372335A